1998
DOI: 10.1063/1.122842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of annealing on self-organized InAs quantum islands on GaAs(100)

Abstract: Articles you may be interested inPresentation and experimental validation of a model for the effect of thermal annealing on the photoluminescence of self-assembled InAs/GaAs quantum dots From large to low height dispersion for self-organized InAs quantum sticks emitting at 1.55 μm on InP (001) Strain relaxation and exciton localization effects on the Stokes shift in InAs x P 1−x /InP multiple quantum wells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The emission blueshift after annealing is the direct consequence of In-Ga intermixing [2][3][4][5][6][7], while the degradation of the PL intensity depends on the InAs coverage [2]. Mo et al observed that, for QDs grown with large InAs coverage, excessive annealing induced strain relaxation by the generation of dislocations and resulted in a decrease of the PL intensity [17]. In our case, the PL intensity does not degrade when the InAs coverage is below ∼2.3 ML (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The emission blueshift after annealing is the direct consequence of In-Ga intermixing [2][3][4][5][6][7], while the degradation of the PL intensity depends on the InAs coverage [2]. Mo et al observed that, for QDs grown with large InAs coverage, excessive annealing induced strain relaxation by the generation of dislocations and resulted in a decrease of the PL intensity [17]. In our case, the PL intensity does not degrade when the InAs coverage is below ∼2.3 ML (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…2(b). The integrated PL intensity of sample A firstly increases when the T a is higher than 700 1C, and then decreases when the T a is higher than 800 1C, indicating a process of defect elimination at T a p800 1C [10] and the generation and multiplication of dislocations induced by strong strain relaxation in the sample at T a X850 1C [11]. The PL linewidth of sample A decreases after RTA treatment, in accordance with the usual RTA treatment results of QDs, which is attributed to the intermixing-induced narrowing of the distribution of density of states of nanostructures [7,8,12].…”
Section: Resultsmentioning
confidence: 97%
“…The active (QD) and overgrown layers, however, have different growth temperature requirements: QDs growth temperature is low (approximately 470°C to 520°C) to prevent In desorption, but subsequent overlayer growth temperature is high (580°C and above), especially if the layer contains slow-diffusing species such as Al. The fundamental difference in growth temperature requirements and its inevitability lead to extensive investigation of the properties of InGaAs QDs annealed in situ [ 12 - 15 ] and ex situ [ 15 - 21 ]. In terms of luminescence, it is well established that conventional InGaAs QDs that underwent annealing would: (1) exhibit a blueshift in their ground-state emission, (2) have narrower linewidth, and, in some cases, (3) emit at an increased intensity due to interdiffusion and intermixing of cations and the reduction in non-radiative recombination centers in the surrounding matrix [ 13 - 20 ].…”
Section: Introductionmentioning
confidence: 99%